Impact of Size Distribution of Nanoparticles in TiO2 Paste for its Application in Dye Sensitized Solar Cells - Dhungel, Suresh Kumar; Park, Chang Woo (Himalayan Physics, 2013)
Titanium dioxide (TiO2) nanoparticles have been recognized as a significant candidate for Dye SensitizedSolar Cell (DSSC) applications. A comparative study of the TiO2 films with two different patterns of the nanoparticlessize distribution is reported in this article. Crystallinity of the nanoparticles, distribution of size of nanoparticles and theperformance parameters of the DSSCs fabricated out of the films were thoroughly analyzed for the films of both types of TiO2.The TiO2 film with its nanoparticles distributed over a wider range showed better interconnection between the nanoparticlesand hence less porosity that resulted in lower area available for the adsorption of dye after sintering whereas the TiO2 filmwith its nanoparticles distributed over a narrower range showed relatively poor interconnection between the nanoparticlesleading to enhanced porosity suitable for DSSC application. A proper balance between porosity of the TiO2 film and theinterconnection between the nanoparticles can ensure the DSSC with improved performance parameters. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 27-31 Uploaded date: 12/23/2013